2012
DOI: 10.1002/art.34423
|View full text |Cite
|
Sign up to set email alerts
|

β‐glucan triggers spondylarthritis and Crohn's disease–like ileitis in SKG mice

Abstract: Objective. The spondylarthritides (SpA), including ankylosing spondylitis (AS), psoriatic arthritis (PsA), reactive arthritis, and arthritis associated with inflammatory bowel disease, cause chronic inflammation of the large peripheral and axial joints, eyes, skin, ileum, and colon. Genetic studies reveal common candidate genes for AS, PsA, and Crohn's disease, including IL23R, IL12B, STAT3, and CARD9, all of which are associated with interleukin-23 (IL-23) signaling downstream of the dectin 1 ␤-glucan recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
207
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 228 publications
(217 citation statements)
references
References 49 publications
9
207
0
1
Order By: Relevance
“…They are able to recognize and promote pathogen clearance and induce inflammatory signals. This process seems to follow the Syk and CARD9 pathway which was recently implicated in a mouse model of SpA (Ruutu et al, 2010). The upregulation of CLEC4D, observed for the first time in an expression profiling study of AS patients (Pimentel-Santos et al, 2011), supports the importance of innate immune mechanisms in AS pathology.…”
Section: Lessons From Genomic Profiling In As 21 the Link Between Ansupporting
confidence: 54%
“…They are able to recognize and promote pathogen clearance and induce inflammatory signals. This process seems to follow the Syk and CARD9 pathway which was recently implicated in a mouse model of SpA (Ruutu et al, 2010). The upregulation of CLEC4D, observed for the first time in an expression profiling study of AS patients (Pimentel-Santos et al, 2011), supports the importance of innate immune mechanisms in AS pathology.…”
Section: Lessons From Genomic Profiling In As 21 the Link Between Ansupporting
confidence: 54%
“…PTGER4 then induces the production of IL-23 and IL-17, promoting the expansion of Th17 lymphocytes (Figure 3). 114 It has been reported that when SKG mice are treated with β-glucan they develop spondyloarthritis and Crohn's disease, 115 and that this model is characterised by activation of Th17 cells. 116 This model suggests that involvement of the IL-23 signalling pathway in AS pathogenesis may be triggered by ubiquitous pathogens carrying β-glucan.…”
Section: -111mentioning
confidence: 99%
“…Sakaguchi et al, demonstrated that this mutation altered the threshold of thymic selection thus it increased the pool of self-reactive 27 T cells, which led to spontaneous polyarthritis and bone destruction mimicking RA [158]. [160].…”
Section: -53 Skg Mouse Modelmentioning
confidence: 99%
“…Anti-mouse IL-23 antibody and IL-17 deficiency both prevent the development of peripheral arthritis, spondylitis and ileitis [160].…”
Section: -53 Skg Mouse Modelmentioning
confidence: 99%